Carotid Plaque Neovascularization Detected With Superb Microvascular Imaging Ultrasound Without Using Contrast Media. Issue 11 (November 2019) - Zamani, Mahtab; Skagen, Karolina; Scott, Helge; Lindberg, Beate; Russell, David; Skjelland, Mona
Abstract : Background and Purpose—: A significant proportion of ischemic strokes are caused by emboli from unstable carotid artery plaques with intraplaque neovascularization (IPN) as a key feature of plaque instability. IPN is not detectable with conventional Doppler ultrasound. Contrast-enhanced ultrasound (CEUS) can visualize IPN, but its use is limited in clinical practice because it requires an intravenous injection of contrast. Superb microvascular imaging (SMI) without contrast uses an algorithm to remove clutter and motion wall artifacts while preserving low-velocity blood flow signals, enabling visualization of IPN. Our aim was to assess the feasibility of SMI for the detection of IPN. Methods—: Thirty-one patients with >50% carotid stenosis were included: 22 patients were symptomatic and 9 asymptomatic. All patients underwent conventional carotid ultrasound, CEUS, SMI, and blood tests. CEUS and SMI findings were compared and correlated to histological plaque assessments after endarterectomy. Results—: There was significant positive correlation between an IPN visual 5-level classification of SMI and a semiquantitative analysis of CEUS ( P <0.001, r =0.911). Plaques with higher SMI grades had higher numbers of neovessels quantified at histology ( P =0.041, r =0.460). Hypoechoic plaques had higher grades of IPN on both CEUS and SMI ( P <0.001). Higher visual IPN counts on SMI were associated with (1) increased areas of inflammation ( P =0.043, r =0.457), (2) combined rank scores of granulation tissue, inflammation and lipids ( P =0.02, r =0.494) at histology, and (3) higher peak-intensity values on quantitative CEUS ( P =0.042, r =0.514). Conclusions—: SMI ultrasound can detect neovascularization with accuracy comparable to CEUS, suggesting SMI to be a promising noninvasive alternative to CEUS for the assessment of carotid plaque stability. Abstract : Supplemental Digital Content is available in the text.